JOURNALYZ: An Android-Based Gamification of Bookkeeping Simulation - Erienika Meiling Lompoliu (CogITo Smart Journal, 2021)
Learning process often be a burden for students. Complex concepts in accounting can difficult be if not intimidating even for undergraduate students and gamification of that lesson can be a solution. Numbers of empirical studies has shown that, due to its unique approach, have positive effects for younger audience and could add another channel for students aside the existing conventional media. Journalyz is intended to be a gamified education for undergraduate students studying accounting and evaluating business transactions based on real-world examples. This program will assist students in developing a solid grasp of the business transactions of a merchandising and service firm as well as being acquainted with the many forms of transactional papers used in business. Furthermore, students will learn to assess transactions utilizing business documentation and record them on relevant accounts. The app is build for Android devices so it is handy and simple to be used anywhere.